Short-term outcomes of repair vs. replacement for rheumatic mitral valve disease - Hou, Ming; Zhou, Wei; Zhang, Ning (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe main types of surgery for rheumatic mitral valve disease are traditional percutaneous mitral balloon valvuloplasty (PMBV), mitral valve replacement (MVR) with removal of the original valve, and valve repair with preservation of the original valve. Some studies have shown that mitral valve repair (MVr) has certain advantages compared with replacement.MethodsThe clinical data of 166 patients with rheumatic mitral valve lesions admitted to the Department of Cardiac Macrovascular Surgery of the Affiliated Hospital of North Sichuan Medical College and the Dazhou Third People's Hospital were retrospectively analyzed to compare the hemodynamic changes after mitral valve repair and replacement.ResultsHemodynamic evaluation of MVr: (1) left ventricular end-diastolic diameters (LVEDD), left atrial end-systolic diameters (LAESD), mitral E-wave velocity, left ventricular ejection fraction (LVEF), mitral valve orifice area (MVOA), mitral pressure halving time (PHT), and mean pressure gradient (MPG) at each time point after MVr were improved compared with preoperative values (P < 0.05). (2) There was a significant improvement in the level of mitral regurgitation in MVr patients intraoperatively and at the time of discharge compared with preoperatively (P < 0.05). Hemodynamic evaluation of MVr and MVR: (1) Patients who underwent MVr had significantly lower LVEDD, LAESD, and mitral E-wave velocity than those of patients who underwent MVR at each postoperative time point (P < 0.05). (2) Patients who underwent MVr had lower left ventricular posterior wall thickness at end-diastole (LVPWd) than that of patients who underwent MVR at 3 and 6 months postoperatively (P < 0.05). (3) Patients who underwent MVr had lower LVEF than that of patients who underwent MVR at 6 months postoperatively (P < 0.05). (4) Patients who underwent MVr had lower left ventricular end-diastolic volume (LVEDV) than that of patients who underwent MVR at 3 months postoperatively (P < 0.05).ConclusionsMitral valve repair and mitral valve replacement are effective in the treatment of patients with rheumatic mitral valve disease, with greater hemodynamic improvement after mitral valve repair than replacement and with greater short-term clinical efficacy than valve replacement.